2022
DOI: 10.1002/adhm.202202045
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Doxorubicin‐Induced Mitochondria Apoptosis for the Monodrug‐Mediated Combination of Chemotherapy and Chemodynamic Therapy

Abstract: Doxorubicin (Dox)‐mediated generation of reactive oxygen radicals (ROS) for mitochondrial apoptosis is identified as a new cytotoxic mechanism in addition to the well‐established one via nuclear DNA replication interference. However, this mechanism contributes far less than the latter to Dox therapy. This newly identified pathway to make Dox therapy function like the combination of chemodynamic therapy (CDT) and chemotherapy‐mediated by Dox alone would be amplified. One‐pot nanoconstruction (HEBD) is fabricate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…As shown in Figure A–D, after treatment with AD@PLGA–PEG NPs, the intracellular ROS content increased significantly, and the mitochondrial membrane potential decreased, which indicated that AD@PLGA–PEG NPs could increase intracellular ROS production and destroy mitochondria to increase cell apoptosis. This may be because ABZ is an inhibitor of HIF-1α, which causes HIF-1α downregulation and reduces HIF-1α interference with electron transfer in the mitochondrial respiratory chain, thus providing more electrons for redox reactions. , Simultaneously, ABZ caused oxidative stress, increased the production of ROS, and promoted tumor cell apoptosis. ,, Besides, DOX also increased ROS production, and this result was consistent with the results of many other DOX nanoformulations reported in the literature …”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…As shown in Figure A–D, after treatment with AD@PLGA–PEG NPs, the intracellular ROS content increased significantly, and the mitochondrial membrane potential decreased, which indicated that AD@PLGA–PEG NPs could increase intracellular ROS production and destroy mitochondria to increase cell apoptosis. This may be because ABZ is an inhibitor of HIF-1α, which causes HIF-1α downregulation and reduces HIF-1α interference with electron transfer in the mitochondrial respiratory chain, thus providing more electrons for redox reactions. , Simultaneously, ABZ caused oxidative stress, increased the production of ROS, and promoted tumor cell apoptosis. ,, Besides, DOX also increased ROS production, and this result was consistent with the results of many other DOX nanoformulations reported in the literature …”
Section: Resultssupporting
confidence: 86%
“…39 When DOX enters the mitochondria, electrons are obtained from the electron transport chain (ETC), semiquinone intermediates are formed, and then the electrons are transferred to oxygen (O 2 ) through a redox reaction to produce ROS. 11 Therefore, to explore the antitumor mechanism of AD@PLGA−PEG NPs, we first investigated their intracellular accumulation. As shown in Figure 2E, free DOX•HCl quickly entered the nucleus, while the AD@ PLGA−PEG NPs were mainly distributed in the cytoplasm.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dialysis membrane filter (MWCO: 3500 Da) containing 1 mL RDP/I was immersed in 10 mL buffer solution (pH 7.4, 6.5, or 5.0) and shaken at 37 °C for in vitro release simulation [ 27 ]. The encapsulation efficiency (EE) and loading level (LL) of IR780 are defined as below: EE = (mass of loaded IR780/mass of feed IR780) × 100% LL = (mass of IR780/mass of RDP/I) × 100% …”
Section: Methodsmentioning
confidence: 99%
“…At present, active ingredients (such as anti-inflammatory agents, exosomes, and nanoparticles) provide a feasible strategy for combating chronic inflammation caused by ROS accumulation and accelerating tissue regeneration ( Zhao et al, 2021 ). Among them, natural compound, epigallocatechin-3-gallate (EGCG), the most abundant polyphenolic compound in green tea, has attracted considerable attention recently ( Liu T. et al, 2022 ; Zhichao et al, 2022 ). EGCG has been widely studied and applied in biomedical field due to its superior physical and chemical properties, including anti-inflammatory, anti-oxidant, bactericidal, anti-aging, promoting angiogenesis, anti-cancer effects, and easy crosslinking to prepare hydrogels ( Byun et al, 2021 ; Mi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%